2010
DOI: 10.1161/strokeaha.109.563122
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Baseline Tissue Status (Diffusion-Weighted Imaging Lesion) Versus Perfusion Status (Severity of Hypoperfusion) on Hemorrhagic Transformation

Abstract: for the UCLA-Samsung Stroke CollaboratorsBackground and Purpose-The frequency of hemorrhagic transformation (HT) on gradient echo imaging and its impact on stroke outcomes continues to be debated. We investigated the factors associated with HTs and the influence of the HTs observed on gradient echo imaging on the early course after a stroke. Methods-We analyzed the data from a prospectively maintained registry of patients who were eligible for recanalization therapy. Serial diffusion-weighted imaging and perfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 33 publications
(30 reference statements)
0
46
0
Order By: Relevance
“…In addition, it was very recently reported that perfusion status (severe time-tomaximum delay and low cerebral blood volume) rather than diffusion-weighted imaging lesion volume was associated with HT after revascularization therapy. 5,8 Moreover, a higher rate of HT and infarct growth in patients with poor collaterals in whom therapeutic recanalization was achieved may support the concept of reperfusion injury. 3 Collateral status differs among patients with acute ischemic stroke.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In addition, it was very recently reported that perfusion status (severe time-tomaximum delay and low cerebral blood volume) rather than diffusion-weighted imaging lesion volume was associated with HT after revascularization therapy. 5,8 Moreover, a higher rate of HT and infarct growth in patients with poor collaterals in whom therapeutic recanalization was achieved may support the concept of reperfusion injury. 3 Collateral status differs among patients with acute ischemic stroke.…”
Section: Discussionmentioning
confidence: 93%
“…5 In the present study, we evaluated whether the baseline collateral grade was an important determinant of HT after therapeutic revascularization, capitalizing on the availability of collateral status before intervention.…”
mentioning
confidence: 99%
“…24,38 While arterial spin labeling is an option, it also is more difficult to acquire and results in less accurate perfusion values. [38][39][40] In contrast to adult stroke, where penumbral hypoperfusion is reported, recent studies reported PWI hyperperfusion after neonatal HII. 24 Further, the small size of 11 day-old rat pups makes it difficult to inject contrast agents necessary to do PWI.…”
Section: Discussionmentioning
confidence: 99%
“…Few patients have been studied with detailed brain imaging, 14 only a proportion of whom have received thrombolytic therapy; animal models 19,31 may not recapitulate the human situation, and other data derive from series of late endovascular intervention. 32 Our cohort allowed the study of interactions between 24-hour recanalization, perfusion characteristics, and incidence of both ICH and early brain edema. We found ICH incidence comparable with previous literature; for example, ICH of all kinds in 34% (48% in ECASS- 2 11 ) and SICH in 5.7% (7.7% in a meta-analysis 33 ).…”
Section: Discussionmentioning
confidence: 99%